Dynamics of immune reconstitution in post-allogeneic hematopoietic stem cell transplant patients and effect of potential factors from Pakistani cohort - Muhammad Hussain; Muhammad Zain ul Abdeen Javed; Muhammad Omair Riaz; Mustajab Alam; Mahreen Ali Khan; Raheel Iftikhar (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the dynamics of immune reconstitution by measuring lymphocyte subsets at periodic intervals after allogenic hematopoietic stem cell transplant, and to assess the impact of potential factors influencing immune reconstitution. Method: The retrospective was conducted at the Department of Immunology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from August 2023 to January 2024, and comprised data of patients regardless of age and agender with haematological or immunological diseases who underwent allogeneic hematopoietic stem cell transplant between January 2017 and December 2023. Immune reconstitution was measured using lymphocyte subset analysis by flow cytometry at 3-, 6- and 12-month post-transplant. Data was analysed using SPSS 27. Results: Of the 100 patients with mean age 8.61±8.82 years (range: 0.3-53 years), 63(63%) were males and 37(37%) were females. Lymphocyte subsets showed significant variance across periodic assessments post-transplant. Reconstitution of natural killer cells and cluster of differentiation 8+ occurred rapidly, while cluster of differentiation 3+, 4+ and 19+ achieved it later. Patient age and stem cell dose were significantly associated with cluster of differentiation 4+, 8+, and natural killer cell reconstitution at 12 months post-transplant. Stem cell source and myeloablative conditioning were associated with early recovery of cluster of differentiation 19+ B lymphocytes. Conclusion: Lymphocyte subset recovery following allogeneic hematopoietic stem cell transplantation occurred at varying rates, making it essential to monitor these subsets periodically post-transplant to tailor intervention strategies. Faster reconstitution of T-cell subsets was linked to higher stem cell dose and younger patient age. Key Words: Conditioning regimen, Hematopoietic stem cell transplantation, Immune reconstitution, Lymphocyte subset.